The Role of Principal's Participative Leadership in Building Teachers' Intrinsic Motivation: Impact on Learning Quality - Kusumawati, Erna (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The improvement of learning quality in Indonesia is greatly influenced by teacher performance and the effectiveness of principal leadership. This study aims to analyze the role of participatory leadership by principals in building teachers' intrinsic motivation and its impact on learning quality. We obtained data using a qualitative approach through in-depth interviews with teachers and principals, along with document analysis. The selection of research subjects used purposive sampling because the subjects had to meet several established criteria. To make the qualitative data easier to understand, thematic analysis was employed in this study's data analysis. The results of the study showed that the implementation of participatory leadership through teacher involvement in decision-making and granting autonomy was positively correlated with increased teacher intrinsic motivation (autonomy, competence, connectedness). We observed that teacher intrinsic motivation contributes to improving learning quality through teaching innovation, student interaction, and the development of relevant materials. The principal's participatory leadership was significant in fostering teacher internal motivation, which had a positive impact on the quality of school learning. The implications of the study emphasize the importance of adopting participatory leadership as a strategy for empowering teachers and improving the quality of education.